Analisis kinerja dan tantangan pengembangan Bank Syariah: Perspektif mahasiswa jurusan Hukum Ekonomi Syariah (HES) UIN Maulana Malik Ibrahim Malang - Aulia, Nurul; Ninggar, Qoridhotul Asri; Aminullah, Muhammad Yusuf; Nikmah, Ainin; Wirasaputra, Lalu Muhammad Fahmi (Maliki Interdisciplinary Journal, 2024)
The development of the banking industry, which continues to increase from year to year, must have a balance in terms of performance assessment, where sharia banking performance measurement does not only look at the profit side, but sharia banking as a sharia business entity needs to consider the benefit aspect. From here we take samples from the perspective of students majoring in Sharia Economic Law at UIN Maulana Malik Ibrahim Malang. There are many obstacles that Indonesia faces in developing sharia financial institutions so that they have low competitiveness compared to conventional financial institutions and sharia financial institutions from other ASEAN countries. This research uses qualitative research methods with descriptive analysis techniques. Thus, the aim of ensuring that sharia banking regulations and policies are for sharia banking to suit the needs of the community and the wishes of banking companies. The findings reveal that students are satisfied with sharia bank services because they use sharia contracts, but there are deficiencies in the bank's marketing department so they are less competitive with conventional banks.